Protective Role of Vitamin B1 in Doxorubicin-Induced Cardiotoxicity in Rats: Focus on Hemodynamic, Redox, and Apoptotic Markers in Heart - Rankovic, Marina; Draginic, Nevena; Jeremic, Jovana; Samanovic, Andjela Milojevic; Stojkov, Svetlana; Mitrovic, Slobodanka; Jeremic, Nevena; Radonjic, Tanja; Srejovic, Ivan; Bolevich, Sergey; Svistunov, Andrey; Jakovljevic, Vladimir; et al. (Frontiers in Physiology, 2021)
Up until now, the specific mechanisms involved in doxorubicin (DOX)-induced cardiotoxicity have not been fully elucidated. Since thiamine deficiency is associated with myocardial dysfunction and it might lead to cardiomyopathy, we aimed to investigate whether dietary thiamine (Vitamin B1) supplementation provides cardioprotection and modulates DOX mediated subchronic cardiotoxicity and to determine possible mechanisms of its effects. Study involved 48 Wistar albino rats divided into 4 groups: healthy non-treated rats and healthy rats treated with thiamine, DOX rats without treatment and DOX rats with thiamine treatment. DOX was applied as a single i.p.injection (15 mg/kg), while thiamine treatment lasted 7 days (25 mg/kg/day i.p.). Before and after the treatment hemodynamic changes were monitored in vivo by echocardiography. When the protocol was completed, animals were sacrificed and rat hearts were isolated in order to evaluate cardiac oxidative stress parameters (superoxide anion radical-O2-, hydrogen peroxide-H2O2, nitric oxide-NO-, index of lipid peroxidation-TBARS, superoxide dismutase-SOD, catalase-CAT, reduced glutathione-GSH) and apoptotic parameters (Bax, Bcl-2, caspases). Also, blood samples were collected for serum evaluation of heart enzymes activity (CK-MB, LDH). DOX treatment significantly reduced the ejection fraction, while thiamine treatment led to a minor increase in the DOX-treated group. In that sense, heart oxidative stress markers were significantly increased in DOX-treated rats, while therapeutic dose of thiamine decreased levels of free radicals. Our study demonstrates the promising ameliorative effects of thiamine against DOX-induced cardiotoxicity through modulation of oxidative stress, suppression of apoptosis and possibility to improve myocardial performance and morphometric structure of rats` hearts.